Associated factors to urinary incontinence in women undergoing urodynamic testing - Juliana Cristina Pereira da Silva; Zaida Aurora Sperli Geraldes Soler; Anneliese DominguesWysocki
Abstract OBJECTIVE Analyzing factors associated with urinary incontinence (UI) among women submitted to urodynamic testing. METHOD A cross-sectional study of 150 women attended at a urological center. Data were analyzed using univariate and multivariate statistics. RESULTS White women (79.3%), overweight (45.3%), menopausal (53.3%), who drink coffee (82.7%), sedentary (65.3%), who had vaginal birth (51.4%), with episiotomy (80%), and who underwent the Kristeller maneuver (69%). 60.7% had Urethral Hypermobility (UH). A statistical association was found between: weight change and UH (p = 0.024); menopause, Intrinsic Sphincter Deficiency (ISD) and Detrusor Instability (DI) (p = 0.001); gynecological surgery, ISD and DI (p = 0.014); hysterectomy and all types of UI (p = 0.040); physical activity and mixed UI (p = 0.014). CONCLUSION Interventions and guidance on preventing UI and strengthening pelvic muscles should be directed at women who present weight changes, who are sedentary menopausal women, and those who have undergone hysterectomy or other gynecological surgery. Studies on pelvic strengthening methods are needed in order to take into account the profile of the needs presented by women.